The Influence of ProcessVariables for MillingSculptured Surfaces on Surface Roughness - Abdulrazaq, Mustafa Mohammed (Al-Khwarizmi Engineering Journal, 2020)
Increasing the variety of products that are being designed with sculptured surfaces, efficient machining of these surfaces has become more important in many manufacturing industries. The objective of the present work is the investigation of milling parameters for the sculptured surfacesthat effecting of surface roughness during machining of Al-alloy. The machining operation implemented on C-TEK CNC milling machine. The influence of the selected variables on the chosen characteristics have been accomplished using Taguchi design approach, also ANOVA had been utilized to evaluate the contributionsof each parameter on process outcomes. Three strategies of tool path (Zig, Zig-Zagand follow periphery), and three levels of spindle speeds (1700, 2200 and 2700 rpm), with three feed rates (200, 400 and 600mm/min).The results showed that low surface roughness valuesproducedwith the zig-zag strategy, higher speeds(2700)rpm and lower feed rates (200) mm/min. The analysis of variance approach ANOVA showed that thestrategy oftool paths was the most affecting variables onsurface roughness with percentage of contribution of (42.25 %).